Perencanaan Lanskap Riparian Sungai Bengawan Solo Berbasis Mitigasi di Kabupaten Bojonegoro - Erwin Ismu Wisnubroto; Mochammad Azkari Hisbulloh Akbar; Romualdus Rezeki Senda (http://arl-faperta.ipb.ac.id/, 2026)
Bojonegoro Regency is an area that often experiences flooding because the Bengawan Solo River crosses it as the longest river in Java Island. Bojonegoro Regency is an area prone to flooding due to the overflow of the Bengawan Solo River which occurs every year, especially during the rainy season. This study aims to analyze the riparian landscape of the Bengawan Solo River which are prone to flooding in Bojonegoro Regency and to formulate recommendations for the concept of flood mitigation in the riparian landscape of the Bengawan Solo River in Bojonegoro Regency. The quantitative descriptive research method with overlay analysis using Geographic Information Systems (GIS) was applied to data on slope, soil type, rainfall, altitude, land use, and river buffers. The results of the analysis show that Bojonegoro Regency is divided into four categories of flood vulnerability, with a dominance of non-prone areas of 36,776 ha (35.18%), quite vulnerable 2,050 ha (1.89%), vulnerable 33,449 ha (32.00%), and very vulnerable 32,247 ha (30.85%). However, areas with very vulnerable (30.85%) are concentrated in flat areas with a slope of 0-8% which are generally residential and rice field areas. The proposed flood mitigation recommendations for the Bengawan Solo River riparian landscape in Bojonegoro Regency include determining mitigation zones consisting of a core zone as a Green Open Space, a buffer zone as a protector of the river and ecosystem, and a utilization zone as a settlement that is adaptive to flooding. The results of the analysis show that most of the Bengawan Solo River riparian landscape in Bojonegoro Regency have a fairly to very high level of flood vulnerability, especially in lowland areas that are widely used for settlements and agriculture